Calton point or Catton Point? A misprinted toponym on the Yukon coast - Burn, C. (Christopher R.) (ARCTIC, 2013)
Capt. John Franklin's account of his journey along the western Arctic coast of North America presents two spellings of the toponym he gave to the point at the eastern end of Workboat Passage, the strait between Herschel Island and the mainland. "Pt. Catton" is printed in the text, and "Pt. Calton" on the accompanying map compiled by Lt. E.N. Kendall. One of these must be a misprint. Catton Point and Calton Point have been used by the National Topographic System and on Canadian hydrographic charts. Calton Point was adopted by the Government of Canada for use in November 1962. However, Catton Point is almost certainly the intended toponym after the Rev. Thomas Catton, FRS (c. 1758 -1838), President of St. John's College, Cambridge (1819 -22), and tutor when John F.W. Herschel arrived at the college in 1809. Catton was one of 13 fellows of the Royal Society honoured by Franklin in northern Yukon. No Calton has ever been elected to the Royal Society or included in the Dictionary of National Biography.